Penguatan Humanisme Pendidikan Agama Islam dalam Mewujudkan Merdeka Belajar di Era Society 5.0 - Novita Nur Hamidah; Suwantoro (UIN Sunan Gunung Djati Bandung, 2022)
In order to fix the education system in Indonesia, the government through the Ministry of Education and Culture made a new breakthrough in the form of a policy of independent learning. The concept of independent learning is more focused on an innovative learning process with great attention to the needs of students. Through this policy, it is hoped that there will be